Integrative approach to managing student sports movement at the university: a theoretical aspect - Kharitonov, D.A.; Ponomarev, V.V.; Melnichuk, A.A.; Golm, L.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate and develop the theoretical and programme content of an integrative approach to managing the student sports movement at the university and to recommend it for practical implementation. Methods and structure of the study. The study was conducted from 2024 to 2026 at Siberian Federal University, Krasnoyarsk and at Krasnoyarsk State Medical University, Krasnoyarsk. The total sample size comprised 600 students in years 1-2. The experimental group consisted of 300 students from Siberian Federal University and 300 students of the control group from Krasnoyarsk State Medical University. The comprehensive theoretical and practical analysis made it possible to identify the main factors influencing the increase in activity and mass participation of the student sports movement at the university and to develop the theoretical content of the integrative approach to activating the sports movement among student youth at the university. Results and conclusions. The conducted theoretical study contributed to the development of an integrative approach to activating the student sports movement, including the following organisational-pedagogical blocks: educational-health-improving, mass sports, individual-independent and control. Programme-methodological support for the integrative approach to managing the student sports movement at the university was also developed, containing the following practice-oriented sections: theoretical, practical, individual and diagnostic. The developed theoretical and methodological material of the integrative approach will contribute to increasing the mass participation and activity of the student sports movement in higher education.